Android-Based Learning Media Development of the Condong Legong Keraton Dance and Baris Tunggal Dance - Ni Made Liza Anggara Dewi; A.A. Trisna Ardanari Adipurwa; I Putu Arya Janottama (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
This article discusses the process of developing learning media for Condong dance and Baris Tunggal dance based on Android. Currently, dance learning can be done by using alternative media indirectly. However, existing media tend to be less communicative and require complex tools to use. The data is presented in the form of a description of the basic techniques of women's dance, namely the Condong Legong Keraton dance, and the men's dance, the Baris Tunggal dance which is then analyzed to produce material that is ready to be applied in media that gives users space to access the desired information. The development of learning media for the Condong Legong Keraton dance and the Baris Tunggal dance based on Android consists of three stages. First, identify problems related to the basic material in learning Balinese dance. Second, the process of making this learning media application has several main things, namely the stage of making flowcharts and storyboards. Third, a development that contains activities to make a design into a product and test the validity of the product repeatedly until the product is produced per the specified specifications. Based on the description in this article, it can be concluded that the development of learning media for the Condong Legong Keraton dance and the Baris Tunggal dance based on Android, it presents an alternative to basic learning media for Balinese dance that is flexible and accommodates a variety of materials used in the interactive learning process.